Semiotic Analysis in the Music Video (MV) of Bangtan Sonyeondan's Album: The Most Beautiful Moment in Life - Yesi Irianti (Indonesian Journal Education, 2025)
This study analyzes the music videos of the album "The Most Beautiful Moment in Life" by Bangtan Sonyeondan (BTS) using a semiotic approach. By applying Roland Barthes' theory, this study identifies the elements of signs, namely signifier and signified, as well as the interpretation of meaning through denotation and connotation. The music videos "I Need U," "Run," and "Epilogue: Young Forever" are the focus of the analysis, which depict themes of emotional struggle, self-discovery, and youth experiences. The results of the analysis show that the visuals in the music videos convey not only literal actions but also deeper cultural and psychological meanings, providing insight into how BTS communicates through complex narratives that resonate with their audiences. This study emphasizes the importance of semiotics in understanding the diverse meanings contained in music videos.